Formoxanthone C Inhibits Malignant Tumor Phenotypes of Human A549 Multidrug Resistant-cancer Cells through Signal Transducer and Activator of Transcription 1-Histone Deacetylase 4 Signaling - Chutima Kaewpiboon; Nawong Boonnak; Sirichat Kaowinn; Natpaphan Yawut; Young-Hwa Chung (My University, 2022)
Considering that presence of cancer stem cell (CSC) subpopulation in tumor tissues confers anticancer drug resistance, we investigated whether human A549 lung cancer cells resistant to etoposide possess CSC-like phenotypes. Furthermore, it is known that these malignant tumor features are the leading cause of treatment failure in cancer. We have thus attempted to explore new therapeutic agents from natural products targeting these malignancies. We found that formoxanthone C (XanX), a 1,3,5,6-tetraoxygenated xanthone from Cratoxylum formosum ssp. pruniflorum, at a non-cytotoxic concentration reduced the expression of the signal transducer and activator of transcription 1 (STAT1) and histone deacetylase 4 (HDAC4) proteins, leading to inhibition of CSC-like phenotypes such as cell migration, invasion, and sphere-forming ability. Moreover, we found that treatment with STAT1 or HDAC4 small interfering RNAs significantly hindered these CSC-like phenotypes, indicating that STAT1 and HDAC4 play a role in the malignant tumor features. Taken together, our findings suggest that XanX may be a potential new therapeutic agent targeting malignant lung tumors.
Keywords: HDAC4; HDAC3; STAT1; HDAC1; Histone Deacetylase Inhibitors Research